2021
DOI: 10.1002/bmc.5206
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics reveals the mechanism of quercetin enhancing the bioavailability of ticagrelor

Abstract: Ticagrelor is a first-line clinical drug for the treatment of acute coronary syndrome, but its oral bioavailability is relatively low. Flavonoids (polyphenol compounds commonly found in plant foods) seriously affect human metabolism and health. This study compared the effects of quercetin, luteolin and catechin on the pharmacokinetic parameters of ticagrelor and found that quercetin can significantly increase the C max and area under the curve from time zero to 36 h (AUC 0-36 ) of ticagrelor, that is, querceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…An untargeted metabolomics study conducted on rats to evaluate the synergistic effect of some flavonoids on ticagrelor, an antiplatelet oral therapy that is considered to be one of the first-line oral therapy for atherosclerosis and ACS, found that after enhancing the bioavailability of ticagrelor, the plasma levels of GCA and GUDCA decreased, while DCA levels increased [31]. Another metabolomics study conducted in patients with unstable angina (UA) revealed that GCA could be consider as a plasma metabolic biomarker for this condition [32].…”
Section: Discussionmentioning
confidence: 99%
“…An untargeted metabolomics study conducted on rats to evaluate the synergistic effect of some flavonoids on ticagrelor, an antiplatelet oral therapy that is considered to be one of the first-line oral therapy for atherosclerosis and ACS, found that after enhancing the bioavailability of ticagrelor, the plasma levels of GCA and GUDCA decreased, while DCA levels increased [31]. Another metabolomics study conducted in patients with unstable angina (UA) revealed that GCA could be consider as a plasma metabolic biomarker for this condition [32].…”
Section: Discussionmentioning
confidence: 99%
“…& Vaniot essential oil (AAEO) has been proven to have anti‐inflammatory and antioxidant pharmacological effects (Batiha et al, 2020; Zhang et al, 2023), but its protective effect on LPS‐induced liver injury in mice is still unclear. Therefore, this study planned to use ultra‐performance liquid chromatography tandem mass spectrometry (UPLC‐MS/MS; Zhang et al, 2021) technology to explore the protective effect and mechanism of AAEO on lipopolysaccharide (LPS)‐induced liver injury at the metabolic level.…”
Section: Introductionmentioning
confidence: 99%